Potensi Antibakteri Isolat Actinomycetes terhadap Aktivitas Proteolitik dan Amilolitik Escherichia Coli ATTC 25922 - Bahar, Meiskha; Zulfa, Fajriati (Jurnal Teknologi Laboratorium, 2018)
Occurs E. coli resistance to class 3 cephalosporin class antibiotics and fluoroquinolone groups. The antibiotic resistance that occurs has narrowed the choice of therapy. This study aims to determine the effect of Actinomycetes isolates on proteolytic and amylolytic enzymes E. coli ATCC 25922. This research is experimental research, qualitative tests of protease and amylase enzymes from E. coli ATCC 25922 shown by clear zones around the growing colonies. The result of ANOVA One-Way test showed a significant difference in the width of clear zone, colony zone and PER and AER score with p-value < 0,05. This indicates that Actinomycetes isolates contain compounds that can act as inhibitors of protease and amylase enzymes from E.coli ATCC 25922. It is hoped that there will be research about the identification of Actinomycetes species isolates in Bogor Botanical Garden so that later can be cultivated and produced as an antibiotics alternative.